2020
DOI: 10.1111/hae.14086
|View full text |Cite
|
Sign up to set email alerts
|

Management of pregnancy in women with factor VII deficiency: A case series

Abstract: Factor VII (FVII) deficiency is the most common autosomal recessive inherited bleeding disorder, with an estimated incidence of one per 500 000 cases in the general population. 1 Bleeding manifestations from FVII deficiency are heterogeneous in regard to severity and affected sites and, in many cases, correlate poorly with circulating FVII levels. Based on data from large registry studies, the International Society on Thrombosis and Haemostasis (ISTH) classifies FVII deficiency as: severe, FVII <10% (greatest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 18 publications
(30 reference statements)
0
57
0
1
Order By: Relevance
“…Iron‐deficiency anemia was observed in 17 women (15%), associated with Plummer–Vinson syndrome in one case; 10,15,16,20,25,26,33,35,44 15 of these women had HMB. Only two women with anemia did not report HMB, including one who only exhibited anemia during pregnancy 12,16 …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Iron‐deficiency anemia was observed in 17 women (15%), associated with Plummer–Vinson syndrome in one case; 10,15,16,20,25,26,33,35,44 15 of these women had HMB. Only two women with anemia did not report HMB, including one who only exhibited anemia during pregnancy 12,16 …”
Section: Resultsmentioning
confidence: 98%
“…plasma-derived FVII concentrate (one case), 18 or inducing uterine contraction (four cases), 16,17,57 with uterotonic agents including oxytocin infusion, and intramuscular ergotamine and prostaglandins.…”
Section: Bleeding During Deliverymentioning
confidence: 99%
“…Therefore, the authors recommend that rFVIIa should be made available in the case of hemorrhage or surgical intervention, but not as mandatory prophylaxis. In the research based on a series of five patients, Lee et al suggested that the management of delivery for women with FVII deficiency should be addressed on a case-by-case basis and at centers with expertise in rare bleeding disorders [ 30 ]. In two other recently published articles, peripartum prophylaxis was strongly recommended [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this case is the first ever published on this peculiar clinico-haematological paradox in pregnancy. Despite the fact that several cases with inherited FVII deficiency in pregnancy have been reported in the literature, this has been either in the context of asymptomatic cases that received prophylactic factor replacement to guard against anticipated peripartum haemorrhage, or cases associated with intraoperative bleeding and postpartum haemorrhage 12 14 27–31…”
Section: Discussionmentioning
confidence: 99%